1976
DOI: 10.1111/j.1365-2621.1976.tb00719_41_4.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Analysis, Free Amino Acid, Vitamin and Mineral Content of Microwave Cooked Meat

Abstract: Beef, pork and lamb roasts were cooked by two 2450 MHz microwave ranges, one operated at 220V (1054W cooking power) and one at 1lSV (492W cooking uower) and by a conventional gas oven (163 f 3°C). The only significant effect related to power level of micrdwave ranges was retention of thiamine, riboflavin and niacin which was less in meat cooked by the micro\lave 115V than by the other two methods. There was a trend toward less retention of sodium, chloride, phosphorus and iron in meat cooked by microwaves than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 4 publications
1
5
2
Order By: Relevance
“…Retention of riboflavin in microwave cooked lamb chop samples was above 90% which was in good agreement with the retention values reported by Ang et al (1975) for cooking of beef by four reconstitutional methods. Retention values for microwave cooked lamb chops (97%) was slightly higher than the retention of 88% reported by Baldwin et al (1976) and 89.5% by Bowers and Fryer (1972) for microwave cooked lamb and turkey, respectively.…”
Section: Riboflavincontrasting
confidence: 63%
“…Retention of riboflavin in microwave cooked lamb chop samples was above 90% which was in good agreement with the retention values reported by Ang et al (1975) for cooking of beef by four reconstitutional methods. Retention values for microwave cooked lamb chops (97%) was slightly higher than the retention of 88% reported by Baldwin et al (1976) and 89.5% by Bowers and Fryer (1972) for microwave cooked lamb and turkey, respectively.…”
Section: Riboflavincontrasting
confidence: 63%
“…Almost all previous researchers have found significantly more moisture to be lost by microwave cooking than by conventional cooking of meat (Janicki and Appledorf, 1974;Baldwin et al, 1976;Moore et al, 1980;El-Shimi, 1992). Except for the values in chicken skin and lamb fat, the content of moisture in microwave-cooked meat (chicken and lamb chops) was always lower than the moisture content of meat roasted in the oven.…”
Section: Watermentioning
confidence: 85%
“…Another reason could be the amount of dripping, which probably was proportionally more from the chicken, washing out more fat from the chicken than the lamb chops. Baldwin et al (1976) found that the percent fat in the drippings differed for pork and lamb cooked conventionally and by microwave. There seemed to have been no explanation for this difference in the trends between the two species of meat.…”
Section: Fatmentioning
confidence: 96%
See 1 more Smart Citation
“…Most of the amino acids, including aromatic amino acids, were significantly reduced in quantity during cooking; microwave cooking caused the highest losses in both type of samples (Table 4). A previous study on conventional and microwave cooking of pork, beef and lamb showed that most essential amino acids including leucine, isoleucine, phenylalanine and methionine were affected during cooking (Baldwin, Korschgen, Russel, & Mabesa, 1976).…”
Section: Free Amino Acids In Egg Yolkmentioning
confidence: 99%